Does Class-Based Campaigning Work? How Working Class Appeals Attract and Polarize Voters. (April 2021) - Robison, Joshua; Stubager, Rune; Thau, Mads; Tilley, James
Recent elections have featured various politicians directly appealing to the working class, yet we know little about how citizens react to class appeals from candidates. We investigate this question using survey experiments conducted in the United States and Denmark. We show that symbolic class rhetoric substantially influences candidate evaluations and ultimately polarizes these evaluations across class lines. We also unpack how class appeals work and find that while they increase perceptions of representation among working class voters, they have a more limited effect on perceptions of candidates' ideological position. Our results help explain how class affects voter decision-making and contribute to broader discussions about the role of political elites in activating social cleavages.